Molecular dynamics simulations of polyethers and a quaternary ammonium ionic liquid as CO2 absorbers - Cardoso, Piercarlo Fortunato; Fernandez, Juan S. L. C.; Lepre, Luiz Fernando; Ando, Rômulo Augusto; Costa Gomes, Margarida F.; Siqueira, Leonardo J. A. (The Journal of chemical physics, 2018)
The properties of mixtures of butyltrimethylammonium bis(trifluoromethylsulfonyl)imide, [N4111][NTf2], with poly(ethyleneglycol) dimethyl ether, PEO, were described as a function of PEO chain size by molecular dynamics simulations. Both PEO chain size and mixture composition revealed to play a significant role in determining the structure and the dynamics of the fluids. The remarkably higher viscosity observed for mixtures composed by 0.25 mole fraction of PEO was attributed to the increase in the gauche population of OCCO dihedral of the polyether of longer chains. The negative solvation enthalpy (ΔsolH < 0) and entropy (ΔsolS < 0) revealed a favorable CO2 absorption by the neat and mixture systems. The CO2 absorption was higher in neat PEO, particularly considering longer chains. The gas solubility in the mixtures presented intermediate values in comparison to the neat PEO and neat ionic liquid. The CO2 solutions had their structures discussed in the light of the calculated radial and spatial distribution functions.